Molar Incisor Hypomineralization (MIH) in a Child with Congenital Chronic Intestinal Pseudoobstruction (CIPO) - Mohammed Zameer; Syed Ali Peeran; Syed Nahid Basheer; Syed Wali Peeran; Sameen Badiujjama Birajdar; Faisal Mohammad Alzahrani; Ali Mohammed A. Alkhayrat (Hindawi Limited, 2020)
Molar incisor hypomineralization (MIH) is a qualitative enamel defect of systemic origin affecting 1-4 permanent first molars (PFMs) frequently in association with affected permanent incisors (PIs). The exact etiology of MIH is still unclear but considered to be multifactorial. This present case report to the best of our knowledge is the first case reported which acknowledges MIH in a patient with chronic intestinal pseudoobstruction (CIPO) with underlying neurological disease due to somatic mitochondrial disorder. It also elicits the availability of various contemporary treatment options and their proper selection and early intervention to manage the functional and aesthetic problems caused by enamel defects and to improve the quality of life in the patients.